Concerted regulation of renal plasma flow and glomerular filtration rate by renal dopamine and NOS I in rats on high salt intake. Issue 6 (29th March 2017) - Ibarra, Mariano E.; Albertoni Borghese, Maria F.; Majowicz, Mónica P.; Ortiz, María C.; Loidl, Fabián; Rey‐Funes, Manuel; Di Ciano, Luis A.; Ibarra, Fernando R.
Abstract: Under high sodium intake renal dopamine (DA) increases while NOS I expression in macula densa cells (MD) decreases. To explore whether renal DA and NOS I, linked to natriuresis and to the stability of the tubuloglomerular feedback, respectively, act in concert to regulate renal plasma flow (RPF) and glomerular filtration rate (GFR). Male Wistar rats were studied under a normal sodium intake (NS, NaCl 0.24%) or a high sodium intake (HS, NaCl 1% in drinking water) during the 5 days of the study. For the last two days, the specific D1 ‐like receptor antagonist SCH 23390 (1 mg kg bwt −1  day −1, sc) or a vehicle was administered. HS intake increased natriuresis, diuresis, and urinary DA while it decreased cortical NOS I expression ( P  < 0.05 vs. NS), Nicotinamide adenine dinucleotide phosphate diaphorase (NADPH‐d) activity in MD ( P  < 0.001 vs. NS) and cortical nitrates+nitrites (NOx) production (NS 2.04 ± 0.22 vs. HS 1.28 ± 0.10 nmol mg protein −1, P  < 0.01). Treatment with SCH 23390 to rats on HS sharply decreased hydroelectrolyte excretion ( P  < 0.001 vs. HS) while NOS I expression, NADPH‐d activity and NOx production increased ( P  < 0.05 vs. HS for NOS I and P  < 0.001 vs. HS for NADPH‐d and NOx). SCH 23390 increased RPF and GFR in HS rats ( P  < 0.01 HS+SCH vs. HS). It did not cause variations in NS rats. Results indicate that when NS intake is shifted to a prolonged high sodium intake, renal DA through the D1 R, and NOS I in MD cells act in concert to regulate RPF and GFR to stabilize the delivery of NaCl to the distal nephron. Abstract : Concerted regulation of renal plasma flow and glomerular filtration rate by renal dopamine and NOS I in rats on high salt intake. Under high sodium intake renal dopamine (DA) increases while NOS I expression in macula densa cells (MD) decreases. Aim : To explore whether renal DA and NOS I, linked to natriuresis and to the stability of the tubuloglomerular feedback, respectively, act in concert to regulate renal plasma flow (RPF) and glomerular filtration rate (GFR). Results indicate that when NS intake is shifted to a prolonged high sodium intake, renal DA through the D1R, and NOS I in MD cells act in concert to regulate RPF and GFR to stabilize the delivery of NaCl to the distal nephron.